Alih Kode dan Campur Kode dalam Novel Kambing dan Hujan Karya Mahfud Ikhwan - Septriani, Hilda (Universitas Andalas, 2025)
Literary works have an essence as a medium of communication between the author and the reader. Authors write their creative ideas based on their experiences and record the dynamics of the society around them. In general, the author raised some characteristics, both in storytelling techniques and the use of local language as an identity. This study aims to reveal the phenomenon of code-switching and code-mixing in Mahfud Ikhwan's